Primary malignant melanoma of the nose: an unusual presentation - Gupta, Yashita; Memon, Mohd. Jafar; Gahine, Renuka (International Journal of Research in Medical Sciences, 2017)
Mucosal malignant melanoma of the nasal cavity and paranasal sinuses is a rare entity. It is an unusual cause of nasal obstruction and epistaxis seen especially in elderly. We report the case of a primary nasal malignant melanoma in a 32 year old woman who presented with the history of epistaxis for 1 month. In our knowledge, this is the first case of primary nasal malignant melanoma to be reported in this age group.